Dinggo Sedaya website: Innovation in digital learning resources for early children's education - Salehuddin, Shafira Nurulita; Putra, Yudithia Dian; Anisa, Nur; Pramono, Pramono; Arifin, Imron (Universitas Negeri Yogyakarta, 2024)
Digital learning resources aim to be a container or reference that can be used as a support to develop existing learning tools. In addition, current technological advances make learning resources one of the containers that can improve digital literacy competencies for its users. Technology mastery skills are key in utilizing digital technology. However, it is unfortunate that digital learning resources are not utilized properly due to limited technology usage skills, especially in learning. In addition, the lack of digital learning resources for early childhood education is one of the limitations in adjusting digital learning resources for Early Childhood Education teachers. This study itself aims to create an efficient, effective, and attractive website product to be used as a digital learning resource for in-depth early childhood education. Data collection methods used include interviews, observations, and filling out questionnaires. This study uses the Research and Development (R&D) method by implementing the ADDIE design. The sample in this study was thirty Early Childhood Education teachers. The results of the study showed that the Dinggo Sedaya website is suitable to be used as a digital learning resource for in-depth early childhood education. Based on the results of validity and feasibility, the Dinggo Sedaya website is valid and suitable for use. This study implies that the Dinggo Sedaya website can be accessed by teachers as a digital learning resource for developing learning tools and improving the digital literacy competencies of Early Childhood Education teachers. Further research is expected to be able to examine the development of digital learning resources more broadly to provide a comprehensive picture and become the basis that digital learning resources need to be developed to support more meaningful learning in early childhood.